МЕТОД ВИЗНАЧЕННЯ АСИМЕТРІЇ ТРИФАЗНОЇ НАПРУГИ ОСНОВНОЇ ЧАСТОТИ І ВИЩИХ ГАРМОНІК - Маков, Д.К. (Інститут електродинаміки НАН України, Київ, 2018)
The new method of digital determination of symmetric phase-sequence system of three-phase electric voltages is presented. It uses the next operations: tuning multiple three frequency of measuring of instantaneous values to fundamental frequency of network voltage; analog-digital transformation of instantaneous values of three networks voltages and memorized it; selection of codes that contain the sought after symmetric phase-sequence; selection of codes of voltage of fundamental frequency. A method differs in simplicity and exactness.  References 10, figures 3.